Strategies for Inclusive Teaching of Mathematics in Basic Education: Systematic Review: Estrategias de Enseñanza Inclusiva de las Matemáticas en Educación Básica: Revisión Sistemática - Uribe Dorantes, Alejandra Elizabeth (2022)
In recent years, inclusive education began to be part of the objectives of various governments around the world. In contrast, mathematics has been positioned as one of the most complex sciences for students because of its traditional teaching and far removed from the learning characteristics of students; this has generated the interest to inquire about the inclusive mathematics teaching strategies that favor its understanding. In view of this, the present research aimed to carry out a systematic review that gathered and analyzed those studies that inquired about effective inclusive teaching strategies for teaching mathematics at the basic level. For its search, a period of 11 years (2010-2011) was established, inclusion and exclusion criteria were determined and databases were consulted using various search strings. It was concluded that the publication of articles has fluctuated over the years, with Spain being the country with the highest number of productions. In the same way, three different ways of approaching the subject and 26 Strategies for inclusive teaching were found.